Divergent Carcinogenic Risks of Domestic versus Ritual Combustion on Nasopharyngeal Carcinoma in Bali: A Matched Case-Control Study - Made Prani Windasari; I Gde Ardika Nuaba; Made Lely Rahayu (HM Publisher, 2026)
Nasopharyngeal carcinoma (NPC) is endemic in Indonesia, particularly among the ethnically distinct Balinese population. The interplay between Epstein-Barr virus (EBV) and environmental co-factors remains critical to its pathogenesis. A unique cultural duality exists in Bali regarding inhalant exposure: the utilitarian combustion of firewood and tobacco versus the ritual combustion of incense. This study aims to distinguish the carcinogenic risks of these disparate smoke sources using robust statistical methods to account for sparse data bias. A matched case-control study was conducted at a tertiary referral center in Denpasar, Bali. Forty-two patients with histopathologically confirmed WHO Type III Undifferentiated NPC were matched by age and sex with 42 non-cancer controls screened via Digby score. Exposures to firewood, passive and active smoking, and ritual incense were assessed. To address quasi-complete separation due to high exposure prevalence, Firth’s Penalized Likelihood Logistic Regression was employed to determine Adjusted Odds Ratios (AOR). Firewood smoke exposure emerged as the predominant risk factor (AOR 14.21; 95% CI 4.82–42.15; p < 0.001), significantly higher than previously estimated by standard models. Passive smoking was confirmed as a substantial independent risk factor (AOR 11.54; 95% CI 3.91–33.82; p < 0.001). Conversely, despite universal usage, ritual incense exposure showed no association with NPC (AOR 0.92; 95% CI 0.35–2.41; p = 0.865), likely due to the open-air ventilation of Balinese shrines. Salted fish consumption remained a significant co-factor (AOR 6.80; p = 0.002). In conclusion, the study establishes a clear etiological hierarchy: chronic domestic pollutants such as biomass and tobacco smoke are potent drivers of NPC in Bali, likely acting as tumor promoters via EBV reactivation. Ritual incense, in the context of Balinese architecture, is not a significant risk. Public health interventions must prioritize healthy kitchen ventilation and tobacco control.